Doing Participatory Research with Disabled People in Kuwait - Hussain Mohammed Alenaizi (Disability Studies Quarterly, 2018)
This paper explores the experiences of participatory PhD research with six disabled people in Kuwait. The contributors participated in my PhD project (which was conducted with the University of Manchester) as co-researchers. The paper attempts to answer the following questions: What are the co-researchers' motivations behind participating in this research? Do the co-researchers believe that they will benefit from this process and if so, how? What are our (i.e. the researcher and the co-researchers) experiences of the process of participatory research? The findings highlight the process of participatory research with the co-researchers and highlight the issues of power relations, skills development and reciprocity, decision-making processes and sharing experiences, and the possibility of this research opening the door for further research and attitudinal change.
Keywords: Kuwaiti context; participatory research; emancipatory research; inclusive research; reflexivity